THE LINGUO-COGNITIVE PARADIGM OF KAZAKH AND UZBEK PEDAGOGICAL DISCOURSE IN THE EARLY 20TH CENTURY: BASED ON THE WORKS OF M. ZHUMABAYEV AND A.AVLONI - Akimbekova, Shyryn Adilkairovna; Dosmailova, Aigul Nurkeshovna (SCIENCE and SOCIETY, 2026)
The article provides a comparative study of the linguo-cognitive features of the Kazakh and Uzbek pedagogical discourse of the early 20th century, based on the terminological systems in the works of M.Zhumabayev and A.Avloni. The research aims to reveal the semantic nature of pedagogical, psychological, and logical concepts within the texts of both authors and to evaluate their cognitive role in the formation of national educational schools. The study employs conceptual analysis, linguo-cognitive modeling, and comparative-typological methods.